2009
DOI: 10.1073/pnas.0813335106
|View full text |Cite
|
Sign up to set email alerts
|

Purified hematopoietic stem cell allografts reconstitute immunity superior to bone marrow

Abstract: Antigen-specific immune responses are impaired after allogeneic hematopoietic cell transplantation (HCT). The events contributing to this impairment include host hematolymphoid ablation and donor cell regeneration, which is altered by pharmacologic immune suppression to prevent graft-versus-host disease (GVHD). A generally accepted concept is that graft T cell depletion performed to avoid GVHD yields poorer immune recovery because mature donor T cells are thought to be the major mediators of protective immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…The data presented here and elsewhere (25) contradict the conventional view that grafts of rigorously purified stem/progenitor cells will produce inferior immunity, and suggest that such conclusions should be re-examined. The body of data demonstrating the deleterious effects of GVHR on BM and lymphoid function (13)(14)(15)(16)(17)(18)(19)(20)(26)(27)(28) is often overlooked or underestimated.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The data presented here and elsewhere (25) contradict the conventional view that grafts of rigorously purified stem/progenitor cells will produce inferior immunity, and suggest that such conclusions should be re-examined. The body of data demonstrating the deleterious effects of GVHR on BM and lymphoid function (13)(14)(15)(16)(17)(18)(19)(20)(26)(27)(28) is often overlooked or underestimated.…”
Section: Discussioncontrasting
confidence: 46%
“…The body of data demonstrating the deleterious effects of GVHR on BM and lymphoid function (13)(14)(15)(16)(17)(18)(19)(20)(26)(27)(28) is often overlooked or underestimated. We previously reported that even low amounts of T cells cause subclinical, yet lympho-depleting, GVHR (25). Here, we focused on an mHA-antigen-mismatched strain combination and used grafts that allowed us to distinguish between "new" HSC-derived hematopoiesis versus expansion of donor lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the main function of facilitating cells was reported to be the induction of recipient Tregs which in turn promote bone marrow engraftment [72]. Interestingly, another study suggested purified HSCs to be superior compared with unseparated bone marrow in terms of both GVHD avoidance and lymphoid recovery and therewith antigen-specific immune responses post-HSC transplantation [73].…”
Section: Risk Of Graft-versus-host Diseasementioning
confidence: 99%
“…[33][34][35] Moreover, murine studies provide evidence that allogeneic T-cells impair hematopoietic reconstitution after HCT. 36,37 On the other hand, CD62L − effector memory T-cells have been shown to promote donor BM stem/progenitor-derived T-cell reconstitution. 23 In our study, in contrast to SC, aTh-1 cell therapy induced mild, transient suppression of donor hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%